Analysis of Electrical and Mechanical Properties of Self-Sensing Cement Composite with Carbon Microfiber - Stephanie Cucolo Marçula; João Batista Lamari Palma e Silva; Camila Tiemi Ozaki e Silva; Rosa Cristina Cecche Lintz; Luísa Andréia Gachet (Materials Research)
Self-sensing cementitious composites have attracted significant attention in Structural Health Monitoring (SHM) due to their semiconductive and piezoresistive properties, achieved through incorporations conductive fillers such as graphite powder and carbon microfibers. This study evaluated cementitious composites with 0.4%, 0.6%, 0.8%, and 1% of carbon microfibers by mass, analyzing their mechanical, electrical, and microstructural properties. The results indicated that higher fiber contents (0.8% and 1%) increase flexural tensile strength and electrical conductivity. Scanning Electron Microscopy (SEM) reveals void formation around fibers due to their sinuosity. Piezoresistivity analysis demonstrate increased sensitivity to mechanical stress, although the linearity and reproducibility of the piezoresistive response decrease at intermediate fiber contents. Overall, findings confirm the feasibility of developing self‑sensing materials for SHM, while underscoring the need for further studies on durability and large‑scale implementation.